PROPOSED SOCIAL MEDIA MARKETING INITIATIVES TO IMPROVE BRAND AWARENESS AND PURCHASE INTENTION FOR PRATISTA - Gusriyansyah (CV. Radja Publika, 2025)
The global skincare industry is booming, driven by rising consumer interest in health, wellness, and sustainability, in Indonesia, increased disposable incomes and the rapid shift to digital platforms have accelerated market growth, local brands like Pratista face stiff competition from both domestic and international players, sespite being recognized for its safe, affordable, and effective products, Pratista has experienced a decline in revenue due to limited brand awareness and challenges in retaining customers in a dynamic digital marketplace. To address these challenges, our research adopted a mixed-methods approach by combining quantitative data from online surveys with qualitative insights from in-depth interviews and focus group discussions, also further contextualized our findings using secondary data from industry reports and academic journals. Analytical frameworks such as PESTEL, Porter’s Five Forces, VRIO, SWOT, and the Marketing Mix (7Ps) were employed to systematically assess both external market dynamics and internal operational capabilities. Our findings indicate that while strict regulatory compliance, rising disposable incomes, dynamic consumer trends among Millennials and Gen Z, and technological advancements like AI diagnostics create significant opportunities, Pratista must overcome issues related to product diversity, premium packaging, and inconsistent social media engagement, backed by stable financial resources, modern clinics, advanced CRM systems, and a customer-centric approach, we recommend an integrated marketing strategy focused on digital advertising, influencer partnerships, content marketing, and community engagement to enhance brand awareness and foster long-term customer loyalty.